Impact of Integrated Nutrient Management on Physical Properties of Pineapple Grown in Existing Agroforestry Practice at Madhupur Garh, Bangladesh - Md. Habibur Rahman; Kazi Kamrul Islam (Journal of Agroforestry and Environment, 2025)
This study evaluates the impact of Integrated Nutrient Management (INM) on the physical growth parameters and fruit yield of pineapple (Ananas comosus cv. Giant Kew) cultivated under an agroforestry system in Madhupur Garh, Bangladesh. Conducted over a 17-month period (February 2023–July 2024), the field experiment employed a Randomized Complete Block Design (RCBD) with four treatments: T1 (Recommended Fertilizer Dose), T2 (Mulching + 75% FRG), T3 (Mulching + 50% FRG), and T4 (Farmer’s Practice). Data on plant height, leaf dimensions, number of leaves and propagules, fruit length, diameter, weight, days to maturity, and number of marketable fruits per plot were collected and analyzed using Statistix 10 software. The results revealed that the T2 treatment (Mulching + 75% FRG) significantly outperformed other treatments across most parameters. T2 plants exhibited the greatest height (94 cm), highest leaf number (55), longest fruit (17.46 cm), and heaviest fruit (1720 g), while also achieving the earliest maturity (121 DAF) and the highest number of marketable fruits per plot (61). In contrast, T4 (control) consistently recorded the lowest performance across most parameters. These findings highlight the synergistic benefits of combining reduced chemical fertilizer inputs with organic practices such as mulching in pineapple-based agroforestry systems. The study underscores INM as a viable and sustainable alternative to conventional fertilization, enhancing both productivity and environmental stewardship. Recommendations derived from this research support improved nutrient use efficiency and practical, farmer-friendly approaches to sustainable pineapple cultivation in Bangladesh’s agroforestry contexts.